2007
DOI: 10.3748/wjg.v13.i9.1460
|View full text |Cite
|
Sign up to set email alerts
|

Rectal angiolipoma: A case report and review of literature

Abstract: Angiolipoma is a rare vascular variant of the benign lipomatous tumors and is generally seen in subcutaneous tissues. We report a 70-year-old female with abdominal distension not related to rectal small polypoid mass with peduncule described as angiolipoma by histologically, and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In a literature review, we found only 22 cases of angiolipomas involving the gastrointestinal tract. Of these, one was located in the esophagus [6], three in the stomach [7-9], two in the duodenum [10,11], six in the small intestine [12-17], three at the ileocecal junction [18-20], five in the colon [3,10,21-23], and two in the rectum [24,25]. Angiolipomas in the gastrointestinal tract usually do not have specific clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, we found only 22 cases of angiolipomas involving the gastrointestinal tract. Of these, one was located in the esophagus [6], three in the stomach [7-9], two in the duodenum [10,11], six in the small intestine [12-17], three at the ileocecal junction [18-20], five in the colon [3,10,21-23], and two in the rectum [24,25]. Angiolipomas in the gastrointestinal tract usually do not have specific clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, lipomas, lipomatosis, lipoblastoma, lipoblastomatosis, angiolipomas, and myolipomas are considered benign adipose tissue tumors (6). Angiolipomas show iso-hyperintensity on T1-weighted images and hyperintensity on T2-weighted images of magnetic resonance imaging (MRI), and most lesions develop with contrast medium administration (8).…”
Section: Discussionmentioning
confidence: 99%
“…Angiolipomas comprise 5-17% of lipomas (6). It is mostly accepted by the authors that angiolipomas may be developed by embryonic sequestration of multipotential mesenchymal cells, and puberty activates this process via hormones (7).…”
Section: Discussionmentioning
confidence: 99%
“…Angiolipomas occur predominantly about the trunk and extremities in young to middle-aged adults, and in distinction from simple lipomas they are more often associated with pain. Angiolipomas of the gastrointestinal tract are rare, though they have been described and reported to occur from the oesophagus to the rectum 3. Colonic angiolipomas are particularly rare, though when they occur, presentation most commonly includes lower gastrointestinal bleeding, followed by obstruction or pain 4 5.…”
Section: Discussionmentioning
confidence: 99%